Social studies for the twenty-first century methods and materials for teaching in middle and secondary schools - Zevin, Jack (Routledge, Taylor & Francis Group, 2023)
"Now in its 5th edition, this popular text offers practical, interesting, exciting ways to teach social studies and a multitude of instructional and professional resources for teachers. Theory, curriculum, methods, and assessment are woven into a comprehensive model for setting objectives; planning lessons, units, and courses; choosing classroom strategies; and constructing tests for some of the field's most popular and enduring programs. "Build Your Own Lesson" additions to each chapter encourage improvisation and inquiry-based teaching and learning across subjects. A Companion Website offers additional resources for pre-service and practicing social studies teachers"--